DMDS: Best Practices for Managing Data in your Research. - Pratt, Isaac (My University, 2021)
In this introductory workshop, learn about research data management best practices and how investing a small amount of time in organizing your data now can save you a lot of time and prevent future headaches. We will go over best practices for data planning, storage, organization, preservation, and sharing.
Keywords: Research Data Management